2016
DOI: 10.3390/su8040326
|View full text |Cite
|
Sign up to set email alerts
|

Recent NDVI-Based Variation in Growth of Boreal Intact Forest Landscapes and Its Correlation with Climatic Variables

Abstract: Intact Forest Landscape (IFL) is of great value in protecting biodiversity and supporting core ecological processes. It is important to analyze the spatial variation in the growth dynamics of IFL. This study analyzed the change of the Normalized Difference Vegetation Index (NDVI) during the growing season (April-October) for boreal (45˝N-70˝N) IFLs and the correlation with climatic variables over the period of 2000-2013. Our results show 85.5% of boreal IFLs did not show a significant change in the NDVI after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Moreover, path analysis was applied to investigate direct effects of the environmental variables on IAV of ET pixel by pixel over the study area. In the analysis, path coefficients were standardized weights which can be used in examining the possible causal linkage between statistical variables [44][45][46]. In the present work, SD ET was employed as the dependent variable, indicating IAV of ET.…”
Section: Path Analysismentioning
confidence: 99%
“…Moreover, path analysis was applied to investigate direct effects of the environmental variables on IAV of ET pixel by pixel over the study area. In the analysis, path coefficients were standardized weights which can be used in examining the possible causal linkage between statistical variables [44][45][46]. In the present work, SD ET was employed as the dependent variable, indicating IAV of ET.…”
Section: Path Analysismentioning
confidence: 99%
“…Interestingly, multiple reports from both in situ and satellite observations indicated that since 2000, the advancing trends of the SOS have slowed down, with even a reverse trend occurring in some regions [3,11,12]. Meanwhile, for changes in vegetation greenness, a slowed and even reverse trend was also reported in different regions over the Northern Hemisphere after 2000 [13,14]. Considering that changes in vegetation may also lead to multiple feedbacks to the climate system [15], it is necessary to conduct further research on vegetation dynamics after 2000 to understand global climate change.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in snow cover phenology may have significant impacts on vegetation dynamics for several reasons. First, although there is no direct relationship between snow and vegetation growth [21], changes in snow cover can have cascading effects on the known drivers of vegetation growth, such as the chilling requirement, forcing temperatures, and soil moisture status [13,15,16]. Second, changes in snow cover play a very important role in energy feedback through albedo, surface heating, and water budgeting [23,25].…”
Section: Introductionmentioning
confidence: 99%
“…Third, the impact of climate on the ecosystem must be considered by using past data. Climate was not considered in this study, but this factor significantly influences forest fragmentation and loss [22,41,42].…”
Section: Limitations and Further Studiesmentioning
confidence: 99%